2014
DOI: 10.33394/hjkk.v2i2.647
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi Antara Keterampilan Proses Sains Dengan Hasil Belajar Mahasiswa Pada Praktikum Sifat Koligatif Larutan

Abstract: Praktikum yang dilakukan sejauh ini memang sudah memiliki keterampilan proses sains untuk dinilai. Namun, penilaian yang dilakukan belum maksimal. Mahasiswa masih sangat bergantung pada koordinator praktikum, sehingga keterampilan proses sains yang dimiliki mahasiswa tidak berkembang. Pada hakikatnya keterampilan proses sains tersebut dapat meningkatkan hasil belajar. Penelitian ini bertujuan untuk mengetahui apakah ada korelasi antara keterampilan proses sains dengan hasil belajar mahasiswa pada praktikum sif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The correlation coefficient is 0.557, indicating that the level of contribution is moderate, and SPS has a positive correlation with learning outcomes. These findings are in line with the study presented by Najmah et al, (2014), which also found that SPS in the colligative properties of solutions positively correlates with learning outcomes. The same thing was also said by Khairi et al, (2016) that there was a positive relationship between SPS and student LO.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The correlation coefficient is 0.557, indicating that the level of contribution is moderate, and SPS has a positive correlation with learning outcomes. These findings are in line with the study presented by Najmah et al, (2014), which also found that SPS in the colligative properties of solutions positively correlates with learning outcomes. The same thing was also said by Khairi et al, (2016) that there was a positive relationship between SPS and student LO.…”
Section: Discussionsupporting
confidence: 92%
“…Students can understand biological concepts through science activities such as science process skills (Güler & Şahin, 2019). Najmah et al, (2014) also stated that SPS makes students creative, active, and skilled in acquiring abilities. Through the process skills possessed, students can hone their mindset so that they can bolster learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely found incompatibility of existing material with the concept. (Najmah, Khaeruman & Khery, 2014).…”
Section: Discussionmentioning
confidence: 99%